2005
DOI: 10.1016/s0301-0546(05)73248-1
|View full text |Cite
|
Sign up to set email alerts
|

Rebound phenomenon to systemic corticosteroid in atopic dermatitis

Abstract: Three patients with atopic dermatitis, one boy and two girls, aged between 6 and 17 years, presented eczematous skin, pruritus, scarifications, lichenification and a family history of atopy. During exacerbations, the patients sought emergency care and were prescribed oral corticosteroids for a period of approximately 15 days. Initially, the patients improved but after cessation of therapy or dose reduction, marked worsening occurred with the development of lesions with extreme pruritus, several confluent lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Clinical trials have shown that corticosteroid concentrations in the skin following the administration of a potent TCS (clobetasol propionate 0.05%, hydrocortisone 2.3%, or triamcinolone 0.1%) are similar to those achieved with medium doses of oral prednisone 21 . If the skin is severely damaged, however, the distribution of topical treatments is extremely irregular and oral administration is safer and more controllable.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Clinical trials have shown that corticosteroid concentrations in the skin following the administration of a potent TCS (clobetasol propionate 0.05%, hydrocortisone 2.3%, or triamcinolone 0.1%) are similar to those achieved with medium doses of oral prednisone 21 . If the skin is severely damaged, however, the distribution of topical treatments is extremely irregular and oral administration is safer and more controllable.…”
Section: Resultsmentioning
confidence: 96%
“…Rebound flare is frequently observed after the abrupt cessation of systemic corticosteroids. Increased production of IgE by B cells in AD patients has been reported after treatment with oral prednisolone 21 22 . Once clinical improvement has been achieved, it is very important to taper the dosage gradually over time to minimize the likelihood of a rebound effect.…”
Section: Resultsmentioning
confidence: 99%
“…They include diabetes, hypertension, gastric ulcer, osteoporosis, glaucoma and Cushing syndrome. Moreover, increased production of immunoglobulin E (IgE) by B cells in AD patients has been reported after treatment with oral prednisolone, potentially supporting the pathogenesis of extrinsic forms of AD [53–55]. Moreover, the dosage of oral prednisolone during short-term treatment of AD should be accurately tapered to avoid the development of serious relapses and rebound of the disease [53].…”
Section: Methodsmentioning
confidence: 99%
“…Cases of rebound flaring of AD after oral corticosteroids have been reported,91 and this highlights the importance using topical therapy both as a mainstay of therapy and particularly during severe flares which may require more intensive systemic therapy.…”
Section: Systemic Therapies: Overviewmentioning
confidence: 99%